I Can't Keep Your Face and Voice Out of My Head: Neural Correlates of an Attentional Bias Toward Nonverbal Emotional Cues. (4th February 2013) - Jacob, Heike; Brück, Carolin; Domin, Martin; Lotze, Martin; Wildgruber, Dirk
Abstract : Emotional information can be conveyed by verbal and nonverbal cues with the latter often suggested to exert a greater influence in shaping our perceptions of others. The present functional magnetic resonance imaging study sought to explore attentional biases toward nonverbal signals by investigating the interaction of verbal and nonverbal cues. Results obtained in this study underline the previous suggestions of a "nonverbal dominance" in emotion communication by evidencing implicit effects of nonverbal cues on emotion judgements even when attention is directed away from nonverbal signals and focused on verbal cues. Attentional biases toward nonverbal signals appeared to be reflected in increasing activation of the dorsolateral prefrontal cortex (DLPFC) assumed to reflect increasing difficulties to suppress nonverbal cues during task conditions that asked to shift attention away from nonverbal signals. Aside the DLPFC, results suggest the right amygdala to play a role in attention control mechanisms related to the processing of emotional cues. Analyses conducted to determine the cerebral correlates of the individual ability to shift attention between verbal and nonverbal sources of information indicated that higher task-switching abilities seem to be associated with the up-regulation of right amygdala activation during explicit judgments of nonverbal cues, whereas difficulties in task-switching seem to be related to a down-regulation.